Fraudster's and victims' profiles and loss predictors' hierarchy in the mental healthcare industry in the US. (2nd October 2020) - Timofeyev, Yuriy; Jakovljevic, Mihajlo
Abstract: Background: Fraud- or theft-related crimes account for the highest number of crimes in the mental health industry in the US. Aim: This exploratory study aims to demonstrate a fraudster's and respective victims' profiles as well as to identify the loss predictors' hierarchy in the mental health industry in the US. Materials and methods: The Psychiatric Crime database and mixed-effects models are utilized for this purpose. Results: A typical fraudster's profile is defined as a 53-year old male psychiatrist who victimizes one or two of the largest federal insurance programs in states with high property crime ratios. The results revealed the year and state where the fraud is prosecuted explain the largest portion of the variance in loss size. Predictably, case-specific factors also have a significant impact on the loss. Specifically, Medicaid, the existence of collusion, and fraudster's age are associated with the fraud loss. Conclusions: This study empirically justifies considering loss, due to healthcare fraud, from a multi-level perspective. Identified typical fraudster's and respective victim's profiles helped to elaborate on specific practical recommendations aimed at fraud prevention in the mental healthcare system in the US.